Comparative study of nonmotor symptoms in progressive supranuclear palsy and Parkinson’s disease - Ying Chen; Yiming Li; Jieming Huang; Yajing Cai; Xiaochun Chen; Qinyong Ye (BMC Neurology)
Abstract Background Nonmotor symptoms (NMSs) are under-recognized in progressive supranuclear palsy (PSP), despite their considerable impact on quality of life. The full spectrum and impact of NMSs in PSP remain insufficiently understood. This study is aimed to investigate NMSs in patients with PSP and compare the difference of NMSs between patients with PSP and patients with Parkinson’s disease (PD). Methods The study involved 44 patients diagnosed with PSP and 132 patients with PD. NMSs were assessed using a range of evaluation tools. Additionally, the relationship between NMSs and disease severity, as well as the impact on quality of life was analyzed. Results The Non-Motor Symptom Scale (NMSS) and Movement Disorders Society-revised Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) Part I scores were significantly higher in patients with PSP than in patients with PD (42.52 ± 25.64 vs. 32.06 ± 21.45, p = 0.007; 11.89 ± 6.24 vs. 9.80 ± 5.61, p = 0.049). The severity of urinary symptoms was also greater in patients with PSP than in those with PD. Although clinically suspected rapid eye movement sleep behavior disorder (RBD), which was not assessed using polysomnography but rather through RBD Screening Questionnaire, was less common in patients with PSP compared with those with PD, cognitive impairment was more frequent and severe in patients with PSP. Hyposmia, cardiovascular symptoms, constipation, sleep disturbances, emotional symptoms, fatigue, and pain exhibited similar severity and frequency in both patient groups. Only emotional symptoms in patients with PSP were associated with the 39-item Parkinson’s Disease Questionnaire scores, and none of the NMSs were associated with Hoehn & Yahr stage or MDS-UPDRS Part III scores. Conclusion PSP is characterized by a higher burden of NMSs than PD, with some different and common symptom profiles. The impact of emotional symptoms on the quality of life in PSP underscores the importance of addressing these symptoms in clinical care to improve patient outcomes.